(untitled) (Journal of the College of Basic Education, 2026)
The novel represents a phase of the turbulent periods in Iraqi history. We observe that the experience of alienation multiplied within Iraqi society, not only through political displacement but also through the internal displacement of the individual within himself. Qismat was a symbol of a forgotten people with a threatened identity and fragmented characters, living without a homeland to embrace them or an identity to recognize them.